Ordenamento territorial-ambiental na bacia costeira Caueira/Abais - Macedo, Heleno dos Santos (2014)
The processes of development of society and economy in industry and agriculture have led to a rapid degradation of the environment in recent years. These impacts are affecting water resources, mainly by human interference in the watershed areas. Based on this assumption, the present study main objective to analyze the environmental dynamics of coastal watershed Caueira / Abais the perspective of zoning as proposed territorial and environmental planning. To achieve this and other goals outlined specific, we used distinct associated with different steps, such as instruments: bibliographic and cartographic survey and fieldwork. The results of this study show that the basin has different degrees of environmental fragility, due to the characteristics presented by the physical environmental conditions (geology, vegetation, soils, hydrology, among others). Furthermore, it was found that human action over time, through occupation, deployment of infrastructure, real estate speculation and tourist activities has contributed to the degradation process, increasingly evident, especially in environments of beaches Caueira, Abaís and Saco. Thus, this risk of natural, legally constituted, ended in drafting a proposed Zoning Geoenvironmental with the establishment of five zones, namely: Zones of Ecological Protection Areas, Restricted Areas to Use Agricultural Zones, Areas of Conservation Severe, Areas of Interest Tourism / Housing zones Areas and Mineral Exploration, in order to avoid and / or minimize negative consequences that may directly affect the watershed.